MAGNITUDE AND PATTERN OF INJURIES IN PATIENTS VISITING ACCIDENT AND EMERGENCY DEPARTMENT OF COMBINED MILITARY HOSPITAL, RAWALPINDI - A CROSS SECTIONAL STUDY - Siddique, Hamid Jamal; Qureshi, Farhan Muhammad; Tahir, Muhammad; Nasr-e-Alam, Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the magnitude and pattern of injuries and their associated contributory risk factors in patients visiting accident and emergency department. Study Design: Cross sectional study. Place and Duration of Study: Department of Accident & Emergency, Combined Military Hospital, Rawalpindi, from Jun to Sep 2019. Methodology: The sample population comprised of 250 patients with traumatic injuries visiting Accident and Emergency department, Combined Military Hospital, Rawalpindi. A structured questionnaire was used to collect data. Abbreviated Injury Scale was used to assess the injury level of the patients. SPSS version 21 was used for data analysis. Results: Out of 250 patients included in the study, 197 (78.8%) were males and 53 (21.2%) were females. Mean age of the respondents was 36.5 ± 12 years. Most common cause of injury was road traffic accidents being 159 (63.6%). Majority of patients were males between the age group of 25-45 and belonging to rural areas. Two hundred and thirty five (94%) cases of injuries were unintentional. Conclusion: Road traffic accidents were found to be a major contributing factor in un-intentional injury especially among males. Therefore, appropriate preventive strategies must be strengthened and implemented against Road Traffic Accidents. It has been suggested that teenagers and adults must be educated in teaching institutions and at work places to prevent such intentional and un-intentional injuries.